Enterprise Architecture Planning Using TOGAF-ADM at Electronic XYZ Company - Sugianto, Victoria Angela; Rahardjo, Andi Wahju; Chasanah, Nur (Indonesian Scientific Journal, 2023)
Company XYZ is a company engaged in the sale of electronic goods in Purworejo. XYZ company was founded in around 1990 and is one of the oldest existing companies in Purworejo. Currently, it is known that the business processes in the xyz company are still carried out manually. Starting from the process of ordering goods, selling goods, and making reports is still done manually and this company has not used an Application or Information System. This makes it difficult for companies to recap expense reports every month and difficulty in finding data that is needed quickly. Based on these problems, it is necessary to have an application or information system that can be used to facilitate the business processes of xyz companies. To facilitate the creation of applications or information systems, an architectural design is needed. In this study, the company's architectural design will use the TOGAF ADM Architecture, where TOGAF ADM has a framework that can be used to design, evaluate, and build the architecture of a company. The results of this study are in the form of an architectural design that can be used to support business processes and make a recap of expenditure reports at xyz companies.